TWISTERπ – a framework for secure and fast hash functions. (2nd July 2010) - Fleischmann, Ewan; Forler, Christian; Gorski, Michael; Lucks, Stefan
In this paper we present TWISTERπ, a framework for hash functions. It is an improved version of TWISTER, a candidate of the NIST SHA-3 hash function competition. TWISTERπ is built upon the ideas of wide pipe and sponge functions. The core of this framework is a – very easy to analyse – Twister-Round providing both extremely fast diffusion as well as collision-freeness for one internal Twister-Round. The total security level is claimed to be not below 2n/2 for collision attacks and 2n for (2nd) pre-image attacks. TWISTERπ instantiations are secure against all known generic attacks. We also propose two instances TWISTERπ-n for hash output sizes n = 256 and n = 512. These instantiations are highly optimised for 64-bit architectures and run very fast in hardware and software, e.g TWISTERπ-256 is faster than SHA2-256 on 64-bit platforms and TWISTERπ-512 is faster than SHA2-512 on 32-bit platforms. Furthermore, TWISTERπ scales very well on low-end platforms.